2017
DOI: 10.1103/physrevlett.119.157703
|View full text |Cite
|
Sign up to set email alerts
|

Wannier-Mott Excitons in Nanoscale Molecular Ices

Abstract: The absorption of light to create Wannier-Mott excitons is a fundamental feature dictating the optical and photovoltaic properties of low band gap, high permittivity semiconductors. Such excitons, with an electron-hole separation an order of magnitude greater than lattice dimensions, are largely limited to these semiconductors but here we find evidence of Wannier-Mott exciton formation in solid carbon monoxide (CO) with a band gap of >8  eV and a low electrical permittivity. This is established through the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…As Chen et al (2017) reported, N 2 and 13 CO energy levels only overlap in the low wavelength emission range of the MDHL. N 2 ice VUV absorption ranges from 120 nm to 145 nm, and 13 CO ice absorbs photons from 130 nm to 160 nm.…”
Section: Co : N 2 Resultssupporting
confidence: 56%
“…As Chen et al (2017) reported, N 2 and 13 CO energy levels only overlap in the low wavelength emission range of the MDHL. N 2 ice VUV absorption ranges from 120 nm to 145 nm, and 13 CO ice absorbs photons from 130 nm to 160 nm.…”
Section: Co : N 2 Resultssupporting
confidence: 56%
“…With a simple infrared spectroscopic characterisation method available, the spontelectric nature of carbon monoxide (CO) thin films was demonstrated [10]. This turn furnished an explanation for the longstanding problem in the electronic spectroscopy of solid CO [11], and other species (e.g. ammonia [12]), of substantial band origin shifts with deposition temperature through the impact of the electronic Stark Effect on Wannier-Mott excitons within a spontelectric solid.…”
Section: (V)mentioning
confidence: 99%
“…This phenomenon leads to a constant desorption rate of photoproducts that are formed on the ice surface and desorb due to the excess energy of the reaction [33]. We also found the first evidence of excitons in ice exposed to UV irradiation [34]. The observation that only the photons absorbed in the top CO ice monolayers lead to a photodesorption event and the high value of the photodesorption rate suggested that the photodesorption quantum yield, expressed in molecules per absorbed photon, should be higher than unity.…”
Section: Review Of Experimental Resultsmentioning
confidence: 93%
“…We measured the absorption cross-sections of several ice species for the first time, which allowed to estimate the efficiency of photodesorption per absorbed photon in the ice [11,12,13]. We extended this study of CO ice UV-photodesorption to other molecular ice components, and started to explore the effect of soft X-ray irradiation in the photodesorption of ice analogues [14,15,33,34,35,36,37,38,39,40,41,42].…”
Section: Review Of Experimental Resultsmentioning
confidence: 99%